2018
DOI: 10.1039/c8tc01865k
|View full text |Cite
|
Sign up to set email alerts
|

Anthracene-based semiconductors for organic field-effect transistors

Abstract: A review of materials design strategies and efficient study methods for modeling of anthracene derivatives, with a description of their significant application in light-emitting transistors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
129
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 136 publications
2
129
0
1
Order By: Relevance
“…Within the comprehensive review, [31,36] data of >80 n-type OFETs studied in various journals were collected and analyzed for their electronic features and electron mobility. A combination of such materials properties and an efficient data-centric approach would realize regression models of target n-type OFETs properties.…”
Section: Methodsmentioning
confidence: 99%
“…Within the comprehensive review, [31,36] data of >80 n-type OFETs studied in various journals were collected and analyzed for their electronic features and electron mobility. A combination of such materials properties and an efficient data-centric approach would realize regression models of target n-type OFETs properties.…”
Section: Methodsmentioning
confidence: 99%
“…In the past years, it has been used in organic effect transistor (OFET), organic light emitting diode (OLED) and other organic photoelectric devices . Benifiting from its strong modifiability, anthracene derivatives were also synthesized and played important roles in the fields of photochemistry, supramolecular chemistry, photobiology and so on . In 2017, it was found that the mixture of FlAnt , a newly synthesized anthracene derivative and its by‐product 2 A exhibited surprisingly white‐light photoluminescence .…”
Section: Introductionmentioning
confidence: 99%
“…[17] The smallerm emberso ft he acenef amily have been extensively studieda nd are therefore well known in the literature. [18][19][20][21][22][23][24][25][26][27] Pioneering studies on side-chain-substituted acene derivatives by Anthony et al have extended the range of stable, and therefore, synthetically accessible members of the acenef amily to longerm embers. [8,28,29] Following newer thermo-or photochemical approaches to unsubstituted larger acenes, [30][31][32] startingf rom pentacene,a sw ell as matrix-assisted in situ generation techniquesb yB ettinger et al, [33][34][35][36][37][38] the spectroscopic characterisation of larger acenes, up to undecacene, has also become accessible.…”
Section: Introductionmentioning
confidence: 99%